Proximate, Amino Acid Composition and Antibacterial Activity of Woton (Sterculia sp.) Leaves from Raja Ampat, West Papua, Indonesia - Mohammad Sayuti; Iman Supriatna; Intanurfemi B. Hismayasari; Ahmad Yani; Saidin (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2019)
Woton (Sterculia sp.) plant is an endemic plant of Papua and West Papua, Indonesia that has many benefits for the community. This research aims to examine the contents of proximate, amino acid, and antibacterial activity from the leaves extract of two plants namely Sterculia shilinglawii and Sterculia tragacantha. The sample of Sterculia sp. leaves are cleaned, dried, and milled. Then, its chemical composition, amino acid, and bacterial activity are analyzed using a standard procedure. The chemical composition was analyzed using standard AOAC, amino acid was examined using LCMS and antibacterial activity was analyzed using barrier zone against the bacteria that attack the fish. The research results showed that the chemical compositions of Sterculia sp. leaves are carbohydrates, protein, water, ash and fat. The main amino acid contents of woton (Sterculia sp.) leaves are L-Arginine, L-Valine, L-Proline, L-Alanine. Bacterial Test Results showed that woton (Sterculia sp.) leaves extract has intermediate inhibition response against V. algynoliticus. It has been concluded that Sterculia sp. leaves have the potential chemical content.